2022
DOI: 10.1002/widm.1473
|View full text |Cite
|
Sign up to set email alerts
|

Open source intelligence extraction for terrorism‐related information: A review

Abstract: In this contemporary era, where a large part of the world population is deluged by extensive use of the internet and social media, terrorists have found it a potential opportunity to execute their vicious plans. They have got a befitting medium to reach out to their targets to spread propaganda, disseminate training content, operate virtually, and further their goals. To restrain such activities, information over the internet in context of terrorism needs to be analyzed to channel it to appropriate measures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Current studies include predicting and identifying conventional terrorist attacks, email tracking, phone signal information, and social network analytics. Although significant, prediction requires more reliable and intelligent techniques that can handle the complexities associated with each terrorist act while simultaneously allowing for extracting knowledge and predictions from various digital data sources [14]. Terrorism has been of interest to many researchers in many fields.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Current studies include predicting and identifying conventional terrorist attacks, email tracking, phone signal information, and social network analytics. Although significant, prediction requires more reliable and intelligent techniques that can handle the complexities associated with each terrorist act while simultaneously allowing for extracting knowledge and predictions from various digital data sources [14]. Terrorism has been of interest to many researchers in many fields.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Focus of review Main contribution [14] Overview of the open source intelligence (OSINT) cycle in the context of terrorism-related information from various data sources.…”
Section: Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, those people or organizations who are unfamiliar with the nuances of the dark web run the risk of being exposed to potentially harmful or unlawful content. Also, OSINT techniques can be used to gather Tor onion addresses [45] or to research terrorism [46][47] [48].…”
Section: Osint Research Opportunities and Solutionsmentioning
confidence: 99%
“…Mineral wealth and authoritarian governments both played beneficial roles in the events that took place. Two large areas of Eurasia provided the data for their analysis [5]. Using data on terrorist attacks and fatalities from 96 countries, [6] ran a series of multiple regression studies and found no correlation between terrorism and a host of economic and social variables.…”
mentioning
confidence: 99%